DAMPAK PENURUNAN HARGA TBS TERHADAP KEBERLANJUTAN USAHATANI SAWIT DITINJAU DARI TINGKAT KESEJAHTERAAN PETANI SWADAYA DI KABUPATEN MUSI BAYUASIN SUMATERA SELATAN - Riswani; Mulyana, Andy; Tamba, Mora Gibson (Agripita Publisher, 2017)
Fresh Fruit Bunch (TBS) price declines as a result of the volatility in global CPO prices likely to impact farmers in the areas of oil producers, including Musi Banyuasin District in South Sumatera which became one of the oil producers in the province. The impact is most felt is in independent farmers because the price received by independent farmers are not a price which set by the government but the price set between independent smallholders with middlemen. The decline in prices which affects the revenue decline is certainly threatening the sustainability of farming palm forward, especially in the group of independent smallholders. This condition is tested in this study aimed to analyze the impact of price reductions TBS towards sustainability forward through comparative analysis of the condition before and after the price increase TBS. From the research results prove that the decline in TBS production as a result of farming is not done in ideal due to a decreased ability to buy inputs, especially fertilizers. The decline in production and the declining price of TBS continued impact on lower revenue and income of farmers. For strengthening the testing, the results of this study also proves that the received opinion as a result of falling prices make farmers' lives getting away from standard living needs (KHL), wherein the mean average income of farmers for price reductions of Rp2.309.848,19 per family, while the average KHL by Rp3.781.551,81 per month per family. If this condition is not immediately addressed, the behavior of farmers in cultivation of oil palm will move away from the ideal conditions, and farmers are likely to switch to other more profitable farming and leave its oil palm plantations replaced with plants and other businesses